2006
DOI: 10.1007/s00253-006-0500-9
|View full text |Cite
|
Sign up to set email alerts
|

Substrate preference of Bifidobacterium adolescentis MB 239: compared growth on single and mixed carbohydrates

Abstract: The utilization of mono-, di-, and oligosaccharides by Bifidobacterium adolescentis MB 239 was investigated. Raffinose, fructooligosaccharides (FOS), lactose, and the monomeric moieties glucose and fructose were used. To establish a hierarchy of sugars preference, the kinetics of growth and sugar consumption were determined on individual and mixed carbohydrates. On single carbon sources, higher specific growth rates and cell yields were attained on di- and oligosaccharides compared to monosaccharides. Analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
32
0
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(43 citation statements)
references
References 40 publications
10
32
0
1
Order By: Relevance
“…Galactose led to the highest growth rate and cellular yield, whereas glucose was the poorest carbon source for growth. GOS and lactose were both worse growth substrates than galactose but better than glucose, in agreement with a study demonstrating that B. adolescentis MB 239 preferred oligosaccharides over glucose (1).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Galactose led to the highest growth rate and cellular yield, whereas glucose was the poorest carbon source for growth. GOS and lactose were both worse growth substrates than galactose but better than glucose, in agreement with a study demonstrating that B. adolescentis MB 239 preferred oligosaccharides over glucose (1).…”
Section: Discussionsupporting
confidence: 73%
“…In fact, monosaccharides were preferred over oligosaccharides in a few cases (19,24,44), while growth rates and cell yields were higher on disaccharides and oligosaccharides than on their monomeric moieties in many others (1,9,12,13,22,26,43).…”
Section: Discussionmentioning
confidence: 99%
“…In this context, the Bifidobacterium adolescentis-specific growth rate was higher in lactose (Lac) than in glucose (Glc) (15,17), and Bifidobacterium longum NCC2705 preferentially uses Lac over Glc as a carbon source when grown in the presence of both sugars (14). The authors also found the glcP-ptsG locus to be involved in the transport of Glc into the cell, with glcP being downregulated by Lac (14).…”
mentioning
confidence: 88%
“…Some, if not all, dominant intestinal anaerobes preferentially utilize oligosaccharides over mono-and disaccharides (2). Moreover, at least some minor members of the intestinal microbiota grow by cross-feeding on sugars released by the polysaccharide degraders (17,40).…”
Section: Discussionmentioning
confidence: 99%